Influence of Pulsing Electromagnetic Field Therapy on Gene Expression in Muscle Cells, Peripheral Circulation, and Metabolic Factors in Aging Adults - Kóródi, Gyula; Ihász, Ferenc; Rikk, János (Current Chemical Biology, 2016)
This study tested the acute effects of pulsating electromagnetic field (PEMF) therapy session on gene expression in muscle cells, and the changes in cardiovascular and metabolic function in a group of older adults after 12 weeks of treatment. Each therapy session involved 15 minutes of exposure to low frequency pulsating asymmetrical waveforms emitted by the Impulser™ Pro mattress. The treatment was provided five days per week for a total of 60 sessions. Pre and post session muscle biopsies provided tissue for analyses of selected genes. Blood pressure and arterial stiffness was determined for cardiovascular function while cholesterol and glucose levels were evaluated using serum samples. Skin temperature was measured using temperature probes. Fifty-five older men and women (mean age 59.75) completed the entire treatment while six subjects in this group consented to muscle biopsies. The results indicate no change in mRNA content of Ku70 during the single PEMF session however mRNA levels of IL-6 and c-Fos increased. The chronic effects of PEMF treatment include significant reductions in blood pressure, and increases in skin temperature. These findings suggest that due to no change in Ku70 levels, a gene associated with DNA damage, an acute bout of PEMF did not cause acute molecular damage. The increase in IL-6, a gene associated with expression of a glucose transporter, might have an influence on glucose metabolism. The increase in c- Fos, a gene linked to growth factors in skeletal muscle, might influence lose in muscle size associated with aging. The increase in skin temperature is difficult to interpret since it might be linked to either heightened metabolism or improvements in peripheral circulation. More studies are needed to determine if these changes impact the health of aging adults.
Keywords: skin temperature